The study of photovoltaic and electrotransport properties of organic solar cells based on a mixture of PTB7-TH thiophene and PC70BM fullerene - Nurmakhanova, А.; Ilyassov, B.; Alekseev, A.; Yedrissov, A.; Ibrayev, N. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
New samples of organic solar cells (OSCs) based on the recently synthesized polymer, Poly[4,8-bis(5-(2- ethylhexyl)thiophen-2-yl)benzo[1,2-b;4,5-b']dithiophene-2,6-diyl-alt-(4-(2-ethylhexyl)-3-fluorothieno[3,4- b]thiophene-)-2-carboxylate-2-6-diyl)], abbreviated as PTB7-TH have been studied. 6 % energy conversion efficiency was achieved for the standard non-inverted electrode configuration, which corresponds to the international performance for such devices. Local transport of holes in the pure PTB7 film and in the mixture with fullerenes was studied by the probe scanning microscopy in the current spreading mode. Current fluctuations on a nanoscale were revealed in the pure PTB7 film and its mixtures. The current fluctuations can be explained by the influence of the structure on the mobility of holes in the framework of the space-charge limited current (SCLC) model. For the first time, estimates of the variation of the hole mobility in PTB7 were obtained in the framework of a semiempirical model. The method of secondary ion mass spectrometry (SIMS) was used to determine the distribution of the donor and acceptor in the PTB7:PC71BM:DIO film. It was found the enrichment of the surface of the film with a polymer, which explains the better efficiency when using an inverted structure. The method for the investigation of the internal structure of photoactive layers has been developed and was used for the first time, which based on obtaining a cut of the film by a focused ion beam and then subsequent measuring the slice by atomic force microscopy. The achieved quality of the cut exceeds the quality of the cut made by of the ultra microtome used in the previous stages of work. However, the phase contrast of the AFM image shows that the fine structure of the film is damaged by a focused ion beam.
PTB7-TH тиофен жəне PC70BМ фуллерен қоспалары негізіндегі күн ұяшықтарының фотовольтаикалық жəне электртранспорттық қасиеттерін зерттеу
Изучение фотовольтаических и электротранспортных свойств солнечных ячеек на основе смеси тиофена PTB7-TH и фуллерена PC70BМ
Keywords: solar cells (OSCs); confocal optical microscopy; Raman microscopy; organic semiconductors; energy efficiency; bulk heterojunction; electron microscopy; scanning probe microscopy; atomic force microscopy